IMF Adviceon Fiscal Policy. (IMF Working Papers; Working Paper ;, 1989)
IMF advice on fiscal policy is given within a strong accounting framework. Published sources in the last ten years show the direction and change of advice. The treatment of central bank losses, government arrears, and credit subsidies are discussed as examples. Advice on taxation, expenditure, growth, prices, and distribution is examined. Some broad lessons are drawn on sustainability of policy, short- versus long-run policies, and objectivity of advice.